Gram‐scale synthesis of nitrogen‐doped carbon dots from locusts for selective determination of sunset yellow in food samples. (12th November 2021) - Su, Ke; Xiang, Guoqiang; Jin, Xinrong; Wang, Xin; Jiang, Xiuming; He, Lijun; Zhao, Wenjie; Sun, Yaming; Cui, Chen
Abstract: Locust powder was converted into water‐soluble fluorescent nitrogen‐doped carbon dots (N‐CDs) with gram‐scale yield through a self‐exothermic reaction between nitric acid and diethylenetriamine (DETA) within 10 min. The morphology, elemental information, and optical properties of the N‐CDs were characterized using high‐resolution transmission electron microscopy, X‐ray photoelectron spectroscopy, and Fourier‐transform infrared, ultraviolet–visible and fluorescence spectroscopy. Spectroscopic investigation indicated that the fluorescence emission behaviour of N‐CDs is excitation wavelength dependent, with the strongest emission peak at 470 nm using a 390 nm excitation wavelength. The strong absorption peak of sunset yellow (SY) at 482 nm overlaps substantially with the blue emission peak (470 nm) of N‐CDs. This enables the fluorescence emission of N‐CDs to be obviously quenched by SY through the inner filter effect. There was a good linear relationship between the fluorescence quenching degree and the concentrations of SY within the range 0.5–40 μM. The detection limit of developed fluorescence assay for SY is 28 nM, and the relative standard deviation is 2.3% (c = 10 μM). The N‐CDs derived from locusts by the self‐exothermic reaction are highly selective and sensitive fluorescent probes for SY, which were applied to the fluorescence sensing of SY in different food samples with satisfactory results. Abstract : Gram‐scale N‐CDs was efficiently prepared by an exothermic reaction between DETA and nitric acid within 10 min. The blue fluorescence emission at 470 nm of the N‐CDs was effectively quenched by sunset yellow (SY) through an inner filter effect, which made N‐CDs good fluorescent probes for SY in food samples.